2017
DOI: 10.1039/c7ay00756f
|View full text |Cite
|
Sign up to set email alerts
|

Microchip-based 3D-cell culture using polymer nanofibers generated by solution blow spinning

Abstract: Polymer nano/micro fibers have found many applications including 3D cell culture and the creation of wound dressings. The fibers can be produced by a variety of techniques that include electrospinning, the primary disadvantage of which include the requirement for a high voltage supply (which may cause issues such as polymer denaturation) and lack of portability. More recently, solution blow spinning, where a high velocity sheath gas is used instead of high voltage, has been used to generate polymer fibers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The use of fibrous inserts serves to create a 3-D cell culture mimicking the in vivo environment more accurately. 25, 56 Two-dimensional cell cultures do not take the natural 3D environment of the cells adequately into account and often issues arise with the growth media and cell expansion. 27, 57 Cell cultures created within a scaffold are more relevant to cell models and can better simulate the living organism along with the integration to flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of fibrous inserts serves to create a 3-D cell culture mimicking the in vivo environment more accurately. 25, 56 Two-dimensional cell cultures do not take the natural 3D environment of the cells adequately into account and often issues arise with the growth media and cell expansion. 27, 57 Cell cultures created within a scaffold are more relevant to cell models and can better simulate the living organism along with the integration to flow.…”
Section: Resultsmentioning
confidence: 99%
“…In this module, electrospun fibers were incorporated as a 3-D endothelial cell culture scaffold. 25 While most endothelial cell studies are conducted with 2-D cell cultures due to its inexpensive and well-established protocol, issues with the growth media and expansion of cells do pose some limitations. Three-dimensional cell cultures, on the other hand, demonstrate the in vivo microenvironment more holistically and can be integrated to different flow regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells could be imaged on aligned bers, while simultaneously applying a chemical gradient to determine that the cell philapodia respond to a greater extent to the chemical gradient than the alignment of the bers. 94 More recently Chen et al explored ways to incorporate ber scaffolds into a 3D printed microuidic system, 24,95,96 starting with an electrospinning approach to directly coat the inside of a channel with polycaprolactone bers. 95 Since this device was 3D printed in a hard plastic, printed threads could be included to host standard ttings making it easy to connect tubing to the device.…”
Section: Fiber Scaffoldsmentioning
confidence: 99%
“…This same group has also reported a blow spinning set up that produced ber scaffolds on an insert that could be tted into a 3D printed ow channel. 96 Chen et al reported a second technique utilizing electrospinning that used a removable insert covered in bers (Fig. 11).…”
Section: Fiber Scaffoldsmentioning
confidence: 99%
“…The flexibility and speed of airbrushing allow for nearly seamless integration with 3D printing technologies (Behrens et al, ; Chen, Townsend, Sell, & Martin, ). 3D printing has emerged as a means to rapidly create centimeter‐scaled tissue scaffolds with customizable shape and structure (Chia, ; Hutmacher Dietmar et al, ).…”
Section: Introductionmentioning
confidence: 99%